2013
DOI: 10.5812/iranjradiol.11386
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stent Placement of Juxtaanastomotic Stenosis in Native Arteriovenous Fistula After Unsuccessful Balloon Angioplasty

Abstract: BackgroundIn hemodialysis patients, the most common problem in arteriovenous fistulas, as the best functional vascular access, is the juxtaanastomotic located lesions. Percutaneous transluminal angioplasty is accepted as the treatment method for juxtanastomotic lesions.ObjectivesTo assess juxtaanastomotic stent placement after insufficient balloon angioplasty in the treatment of autogenous radiocephalic or brachiocephalic fistula dysfunction.Patients and MethodsBetween July 2003 and June 2010, 20 hemodialysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…It has been shown that the long-term clinical effects after endovascular treatment of obstructive AVF lesions have improved over the past years, and are parallel with our own observations [17,19,[25][26][27][28]. It may be related to the availability of low profile, high pressure balloons and growing experience of interventional teams.…”
Section: Pawel Maga Et Al Endovascular Treatment Of Arteriovenous Fsupporting
confidence: 71%
“…It has been shown that the long-term clinical effects after endovascular treatment of obstructive AVF lesions have improved over the past years, and are parallel with our own observations [17,19,[25][26][27][28]. It may be related to the availability of low profile, high pressure balloons and growing experience of interventional teams.…”
Section: Pawel Maga Et Al Endovascular Treatment Of Arteriovenous Fsupporting
confidence: 71%
“…in 2013 have used metallic stent to treat peripheral venous stenosis in 21 patients with peripheral venous stenosis with VH and demonstrated 1/2-year primary and secondary patency rates of 57.5/40.8% and 76.2%/65.5%, respectively, and these results were comparable to those after balloon angioplasty and surgical shunt revision. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Transluminal angioplasty in the form of balloon dilatation (BD) and endovascular stent (EVS) is a safer alternative to surgery with an advantage of preservation of AVF, but still has unimpressive long-term patency rates. [ 2 3 4 5 6 7 ] When salvage options are exhausted, angiographic embolization of the AVF is another minimal invasive modality in the cases complicated by VH. [ 8 ] We present our experience in management of VH.…”
Section: Introductionmentioning
confidence: 99%
“…Transluminal angioplasty or endovascular stent positioning are a safer alternative to surgery with a higher chance of preserving the AVF, but still with an unimpressive long-term patency rates. 11 , 13 , 24 , 35 , 55 , 60 , 66 DSA offers a high performance in evaluating the severity of arterial stenoses but it is invasive and has a high risk of complication.…”
Section: Dsamentioning
confidence: 99%